A Phase-1b study of tivantinib (ARQ 197) in adult patients with hepatocellular carcinoma and cirrhosis - Santoro, A (Nature Publishing Group, 2013)
BACKGROUND: The mesenchymal-epithelial transition factor (MET) receptor is dysregulated in hepatocellular carcinoma (HCC), and tivantinib (ARQ 197) is an oral, selective, MET inhibitor. METHODS: This Phase-1b study assessed tivantinib safety as primary objective in patients with previously treated HCC and Child-Pugh A or B liver cirrhosis. Patients received oral tivantinib 360 mg twice daily until disease progression or unacceptable toxicity. RESULTS: Among 21 HCC patients, common drug-related adverse events (AEs) were neutropaenia, anaemia, asthenia, leucopaenia, anorexia, diarrhoea, and fatigue. No drug-related worsening of liver function or performance status occurred, but one Child-Pugh B patient experienced drug-related bilirubin increase. Four patients had drug-related serious AEs, including one neutropaenia-related death. Haematologic toxicities were more frequent than in previous tivantinib studies but were manageable with prompt therapy. Best response was stable disease (median, 5.3 months) in 9 of 16 evaluable patients (56%). Median time to progression was 3.3 months. CONCLUSION: Tivantinib demonstrated a manageable safety profile and preliminary antitumour activity in patients with HCC and Child-Pugh A or B cirrhosis.